Reliability and validity of the German version of the DePaul Symptom Questionnaire Post-Exertional Malaise (DSQ-PEM) - Kuczyk, Charlotte; Nöhre, Mariel; Herrmann-Lingen, Christoph; Stolz, Maike; Krauth, Christian; Brähler, Elmar; Jason, Leonard A.; de Zwaan, Martina (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to examine the psychometric properties (reliability and validity) of a German version of the DSQ-PEM, using a representative sample from the German general population (final n = 2,263) and a clinical sample with diagnosed post-COVID-19 condition (PCC) (final n = 1,448).MethodsThe internal consistency of the German version of the DSQ-PEM was calculated separately for both samples using Cronbach’s alpha. Convergent validity was assessed in both samples through correlations between the DSQ-PEM and the Patient Health Questionnaire (PHQ - 4), and for the PCC sample, additionally through a correlation between the DSQ-PEM and the Chalder Fatigue Scale. To evaluate known-group validity, differences in DSQ-PEM scores between the general population sample and the PCC sample were analyzed, adjusting for relevant sociodemographic variables. Additionally, gender- and age-related differences in the DSQ-PEM were calculated separately for both samples.ResultsThe DSQ-PEM items demonstrated excellent internal consistency in both the general population and PCC samples. Higher DSQ-PEM scores correlated with increased symptoms of anxiety and depression in both samples and were also associated with higher scores on the Chalder Fatigue Scale in the PCC sample, indicating good convergent validity. The known-group validity analyses revealed that the German version of the DSQ-PEM effectively differentiates between individuals from the general population and those with PCC, even after adjusting for relevant sociodemographic variables. Advanced age and female gender were associated with higher DSQ-PEM scores in the general population sample. No such correlation was found in the PCC sample.ConclusionIn summary, this study confirms the strong psychometric properties of the German version of the DSQ-PEM and supports the instrument as a reliable and valid tool for measuring PEM in Germany and other German-speaking countries.